Cardboard - TenNapel, Doug. (New York : Graphix, 2012)
When cardboard creatures come magically to life, a boy must save his town from disaster.
Keywords: Heroes -- Comic books, strips, etc; Boys -- Comic books, strips, etc; Paperboard -- Comic books, strips, etc; Magic -- Comic books, strips, etc; Fantasy comics; Graphic novels